Shotgun metagenomic data reveals significant abundance but low diversity of “Candidatus Scalindua” marine anammox bacteria in the Arabian Sea oxygen minimum zone - Villanueva, laura; Speth, Daan R.; vanalen, theo; hoischen, alex; Jetten, Mike (Frontiers in Microbiology, 2014)
Anaerobic ammonium oxidizing (anammox) bacteria are responsible for a significant portion of the loss of fixed nitrogen from the oceans, making them important players in the global nitrogen cycle. To date, marine anammox bacteria found in both water columns and sediments worldwide belong almost exclusively to “Candidatus Scalindua” species. Recently the genome assembly of a marine anammox enrichment culture dominated by “Candidatus Scalindua profunda” became available and can now be used as a template to study metagenome data obtained from various oxygen minimum zones. Here, we sequenced genomic DNA from suspended particulate matter recovered at the upper (170 m deep) and center (600 m) area of the oxygen minimum zone in the Arabian Sea by SOLiD and Ion Torrent technology. The genome of “Candidatus Scalindua profunda” served as a template to collect reads. Based on the mapped reads marine anammox Abundance was estimated to be at least 0.4% in the upper and 1.7% in the center area. Single nucleotide variation (SNV) analysis was performed to assess diversity of the “Candidatus Scalindua” populations. Most highly covered were the two diagnostic anammox genes hydrazine synthase (scal_01318c, hzsA) and hydrazine dehydrogenase (scal_03295, hdh), while other genes involved in anammox metabolism (narGH, nirS, amtB, focA and ACS) had a lower coverage but could still be assembled and analyzed. The results show that “Candidatus Scalindua” is abundantly present in the Arabian Sea OMZ, but that the diversity within the ecosystem is relatively low.